2009
DOI: 10.1152/ajpheart.00952.2009
|View full text |Cite
|
Sign up to set email alerts
|

Differential phosphoinositide 3-kinase signaling: implications for PTCA?

Abstract: CORONARY REVASCULARIZATION by percutaneous transluminal coronary angioplasty (PTCA) has an ϳ90% success rate immediately posttreatment (5). However, the procedure causes vascular injury by endothelial denudation and stretching of the vascular wall, leading to inward vascular remodeling. Endothelial cell (EC) removal exposes the underlying medial vascular smooth muscle cell (VSMC) layer to circulating growth factors and inflammatory cytokines, including platelet-derived growth factor (PDGF), thrombin, thromboxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…17 In contrast, the mechanism of rapamycin is limited to interfering with cellular mitosis, a process tightly regulated by glycosylation-dependent enzymes. 18 Even more unexpected than the observed differences in TLR were the significant interactions present for the relative risks of MI and stent thrombosis between EES and PES according to the presence of diabetes mellitus. Although the increase in restenosis observed in diabetic compared with nondiabetic patients with EES (but not PES) may in part have contributed to its greater rate of MI in this cohort, 19 this mechanism is unlikely to completely explain the loss of the safety benefit for EES in the diabetic group.…”
Section: Discussionmentioning
confidence: 96%
“…17 In contrast, the mechanism of rapamycin is limited to interfering with cellular mitosis, a process tightly regulated by glycosylation-dependent enzymes. 18 Even more unexpected than the observed differences in TLR were the significant interactions present for the relative risks of MI and stent thrombosis between EES and PES according to the presence of diabetes mellitus. Although the increase in restenosis observed in diabetic compared with nondiabetic patients with EES (but not PES) may in part have contributed to its greater rate of MI in this cohort, 19 this mechanism is unlikely to completely explain the loss of the safety benefit for EES in the diabetic group.…”
Section: Discussionmentioning
confidence: 96%
“…A recent pooled patientlevel analysis from the SPIRIT II, SPIRIT III, SPIRIT IV, and COMPARE trials found this interaction to be statistically significant (9). Additional studies are warranted to understand the mechanisms and influence of the glycemic state on the differential vascular responses to rapamycin analogueeluting stents and PES (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Revascularization procedures such as PTCA and placement of stents cause vascular injury, which exposes VSMCs to growth factors PDGF and thrombin, the 2 potent stimulators of VSMCs proliferation and migration and neointimal formation 23. PDGF induces phosphorylation of MEK and ERK, which then induces phosphorylation of Elk.…”
Section: Discussionmentioning
confidence: 99%
“…However, drug‐eluting stents presented with an unexpected problem of an increased rate of in‐stent thrombosis (0.5–3.1%),4, 5, 6, 7, 18, 19 which causes a significantly high 6.3% rate of MI and death 18, 20, 21, 22. This led to a 20% reduction in the use of drug‐eluting stents 23. Thus, despite important improvements in PTCA and placement of drug‐eluting stents to treat CAD and MI, restenosis continues to occur in about 10% of patients and in‐stent thrombosis poses a serious threat to patients.…”
Section: Introductionmentioning
confidence: 99%